Liquidity and Profitability of Commercial Banks in Bangladesh: A Comparison Between Before and After the Covid-19 Crisis (Global Journal of Management and Business Research, 2023)
This study aimed to assess the impact of the COVID-19 pandemic on the liquidity and profitability of commercial banks in Bangladesh. The data of the fifteen selected banks were gathered from the financial statements for each quarter of four years, from Q1 of 2018 to Q4 of 2021, encompassing the two years preceding and following the COVID-19 outbreak. This study uses a comparative quantitative methodology to compare the liquidity and profitability of commercial banks in Bangladesh before and after the COVID-19 pandemic. The results revealed that the profitability, measured by return on asset (ROA), and return on equity (ROE), during post-pandemic times was more volatile than the pre-pandemic time, but the trend is almost the same and the difference is statistically insignificant. The liquidity positions of the banks have been measured by Cash ratio (CaR), current ratio (CR), credit-to-deposit ratio (CDR), debt-toasset ratio (DAR), operating cash flow ratio (OCFR), and debt-to-equity ratio (DER). The results revealed that the pre and post-pandemic liquidity positions are significantly different except for the liquidity measures OCFR, and DER. The findings also confirmed that the COVID-19 pandemic has had a substantial detrimental effect on the liquidity of banks.
Keywords: COVID-19; commercial banks; profitability; liquidity